1976
DOI: 10.1111/j.1432-1033.1976.tb10572.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Degradation and Deamidation of α‐Crystallin Subunits

Abstract: The subunits AA2 and N2, present in α‐crystallin from the nucleus of young and old bovine lenses, were isolated and characterized. It was found that AA2 is identical to a shorter A‐chain and hence it was designated as A1–101. The subunit N2 turned out to be identical with a shorter B‐chain and‐was designated as B1/2−170. Characterization of the subunit N1, present only in α‐crystallin from the cortex of old bovine lenses, suggested that this subunit is a modified B‐chain, probably a deamidation product; it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…The major components of peak 5 were aB1 and aBo; aB2 was a minor component. Both peaks 4 and 5 contained minor components with molecular weights that are consistent with the degradation products reported by Van Kleef et al (1976).…”
Section: Identification Of Crystallins By Esimssupporting
confidence: 70%
See 1 more Smart Citation
“…The major components of peak 5 were aB1 and aBo; aB2 was a minor component. Both peaks 4 and 5 contained minor components with molecular weights that are consistent with the degradation products reported by Van Kleef et al (1976).…”
Section: Identification Of Crystallins By Esimssupporting
confidence: 70%
“…The nomenclature of the m-and P-crystalIins describes whether they are acidic (e.g., aA2, and PA3) or basic (aB2 and f3B2). Early investigators of the lens crystallins attributed the altered electrophoretic mobility of several a-crystallins to deamidation of asparagine (Bloemendal et al, 1972;Stauffer et al, 1974) and C-terminal degradation (Van Kleef et al, 1976). In 1985, Spector et al (1985) showed that radiolabeled phosphate could be incorporated into both &A-and aB-crystallins, with evidence that serine was the only phosphorylated residue.…”
Section: Introductionmentioning
confidence: 99%
“…One manner in which proteins can be marked for degradation is via deamidation [155][156][157]. Acting as a "molecular clock" during physiological conditions, there is suggestion that deamidation may also signal proteolysis with pathogenesis [158,159]. Several studies on individual proteins have shown a significant role for protein deamidation in pathogenesis, including the deamidation of Asp 146 in a B-crystalline, which has been significantly correlated with cataractogenesis [158,159].…”
Section: Mitochondrial Signalingmentioning
confidence: 99%
“…Acting as a "molecular clock" during physiological conditions, there is suggestion that deamidation may also signal proteolysis with pathogenesis [158,159]. Several studies on individual proteins have shown a significant role for protein deamidation in pathogenesis, including the deamidation of Asp 146 in a B-crystalline, which has been significantly correlated with cataractogenesis [158,159]. Proteomics has been used to show that deamidated proteins undergo differential modifications with I/R injury, where fragmentation of deamidated myosin light chain 2 (MLC-2) resulted from ROS generation during reperfusion [88], whilst deami-dated a B-crystalline decreased during the preceding ischemia [160], suggesting further differential proteolysis.…”
Section: Mitochondrial Signalingmentioning
confidence: 99%
“…1B) and is in agreement with previous observations for C-terminal-deleted forms of ␣B-crystallin (34 -37). Removal of the 5 most C-terminal residues generated the A171X mutant and is equivalent to the truncated form of ␣B-crystallin found in normal rat lenses (38), bovine lenses (39), and in rat models of diabetic cataracts (40). Another C-terminal-truncated form of ␣B-crystallin (E164X) has 12 residues removed from the C terminus and this has been detected in normal rat lenses (41).…”
Section: Expression and Purification Of The C-terminal Extensionmentioning
confidence: 99%